(untitled) (Palíndromo, 2020)
This paper investigates the installation “Histórias de aprendizagem” of the chilean plastic artist Voluspa Jarpa Saldías, who undertakes the reading of the archive and its deconstruction, articulating a new interpretation of the past, but above all a different reading of the conception of History, understood as a discontinuity permeated by oblivion and erasure, because what is at stake is the very concept of historical truth. The research undertakes the search of the senses of silence as something that means and that is distinguished from the implicit, which needs the “saying” to put itself in the sense, being possible to think silence and erasure as agents of censorship that concern the which cannot be stated in certain circumstances.